Exploring motivation to notify and barriers to partner notification of sexually transmitted infections in South Africa: a qualitative study - Julia M. Wood; Jane Harries; Moira Kalichman; Seth Kalichman; Koena Nkoko; Catherine Mathews (BMC, 2018)
Abstract Background This article will review qualitative data from intervention-based counselling sessions to explore barriers to partner notification (PN) for South African men and women who have contracted sexually transmitted infections (STIs). This qualitative study took place in a township where there is high STI and HIV prevalence. In addition to reviewing barriers to PN, the study will also identify participants' perceptions about effective PN strategies that are presented during the intervention. Ultimately, the study will assess the intervention's impact on participants' motivation and skills to notify their partners about their STI status. Methods Relying on recorded counselling sessions from an intervention run by a parent study, this sub- study reviewed 30 transcripts from counselling sessions with 15 men and 15 women. The intervention was a 60 min interactive session where STI and HIV education, risk mitigation, and effective PN strategies were discussed. Participants were between 19 and 41 years old (mean age = 28.4) and lived within the catchment area of a South African township. Recordings were chosen based on verbal responsiveness of the participant and were manually coded for analysis. In addition, two programme counsellors were interviewed about their perceptions of the intervention and their experiences with participants to enhance rigour and reduce potential bias. Results By the conclusion of the intervention session, both male and female participants were motivated to notify their partners face-to-face about their positive STI status. Despite this, misperceptions about the etiology and transmission of STIs, as well as inadequate support from the clinical level and power imbalances amongst men and women emerged as major barriers for the prevention of future STIs. Conclusions While the intervention appears to be successful in facilitating partners' intentions to notify, the data shows significant social and structural barriers that will create difficulties for the prevention of future STIs. Participants' persistent concerns about acquiring HIV or their current positive status affect decision-making and therefore, could be a window of opportunity for health-care providers or lay counsellors to discuss STIs in high prevalence areas.